A force-based mechanistic model for describing activated sludge settling process. (15th December 2017) - Xu, Guihua; Yin, Fengjun; Xu, Yuanjian; Yu, Han-Qing
Abstract: Sludge settling as the last step in the biological wastewater treatment process substantially affects the system performance, and thus the design and control optimization of the sludge settling process has been frequently investigated with mathematical modeling tools. So far, these models are developed on the basis of the solid flux theory with numerous parameters and complicated boundary conditions, and their prediction results are often unsatisfactory. In this work, a new force-based mechanical model with five parameters was developed, in which five forces were adopted and Newton's law, rather than the flux theory, was used to describe the sludge settling process. In such a model, the phase interactions were taken into account. New functions of hydrodynamic drag, solids pressure and shear stress were developed. Model validation results demonstrate that both batch and continuous sludge settling processes could be accurately described by this model. The predictions of this model were more accurate than those of flux theory-based models, suggesting its advantages in understanding sludge settling behaviors. In addition, this mechanistic model needed to input 5 parameters and set 1 boundary condition only, and could be directly executed by commercial computational fluid dynamics software. Thus, this force-based model provides a more convenient and useful tool to improve the activated sludge settling design and operation optimization. Graphical abstract: Highlights: A new force-based mechanical model with five parameters was developed. The model was evaluated by batch and continuous sludge settling process. The predictions of our model were more accurate than flux theory-based models. The model involves fewer parameters and convenient to conduct.